A new mfj-type metal–organic framework constructed from a methoxyl derived V-shaped ligand and its H2, CO2 and CH4 adsorption properties. Issue 34 (13th April 2017) - Du, Liting; Lu, Zhiyong; Xu, Li; Zhang, Jinchi
Abstract : A new mfj -type microporous metal–organic framework exhibits high H2, CO2 and CH4 uptake capacities. Abstract : Based on a new V-shaped tetracarboxylic ligand with a methoxyl group, a new mfj -type microporous metal–organic framework [Cu6 (MBDPB)3 (H2 O)6 ]·12DMF·10H2 O (NJFU-3, NJFU for Nanjing Forestry University; H4 MBDPB for 5-methoxyl-1, 3-bis(3, 5-dicarboxylphenyl)-benzene) was successfully synthesized and structurally characterized. With moderately high porosity, appropriate pore aperture and unsaturated metal sites, the activated NJFU-3a exhibits high H2 (2.56 wt% at 77 K and 1 bar) and CO2 uptakes (15.8 wt% at 298 K and 1 bar), and a moderately high CH4 storage capacity of 155 cm 3 cm −3 at 35 bar and 298 K. Meanwhile, it shows a comparably high delivery amount of 135 cm 3 cm −3 when taking 5 bar as a specific lower pressure limit and 65 bar as the upper limit.